Public sector corruption in South Asia: focusing on institutional factors with a two-step fsQCA - Jinwon Han; Chanwahn Kim (Humanities & Social Sciences Communications)
Abstract While the influence of institutions on public sector corruption is widely recognised, empirical exploration of their specific effects remains limited. Using a two-step fuzzy-set qualitative comparative analysis (fsQCA), this paper identifies several causal combinations of political and economic institutions that contribute to higher levels of public sector corruption in South Asia. Based on these findings, we recommend strengthening e-governance to streamline administrative processes, thereby reinforcing the corruption-reducing effects of parliamentarism, which may otherwise be distorted by factors such as excessive bureaucracy in the region. Additionally, we emphasise the need for South Asian policymakers to enhance external audits and integrity assessments by independent agencies while prioritising the improvement of democratic governance as a key strategy for effectively addressing corruption in the public sector.